2012
DOI: 10.1111/j.1744-7909.2012.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate Reductase Isoform 1 is Localized in the Cytosol and Not Peroxisomes in Plant Cells

Abstract: Glyoxylate reductase (GLYR) is a key enzyme in plant metabolism which catalyzes the detoxification of both photorespiratory glyoxylate and succinic semialdehdye, an intermediate of the γ-aminobutyrate (GABA) pathway. Two isoforms of GLYR exist in plants, GLYR1 and GLYR2, and while GLYR2 is known to be localized in plastids, GLYR1 has been reported to be localized in either peroxisomes or the cytosol. Here, we reappraised the intracellular localization of GLYR1 in Arabidopsis thaliana L. Heynh (ecotype Lansberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 92 publications
2
33
0
Order By: Relevance
“…Asterisks indicate the relevant bands. Ching et al, 2012) in N. tabacum suspension-cultured cells (Supplemental Fig. S3B), reconfirming that the XBAT35.2-containing structures were Golgi and not peroxisomes, which generally can resemble one another based on their appearance via confocal microscopy.…”
Section: Xbat352 Localizes Predominantly To the Golgi In Arabidopsismentioning
confidence: 74%
See 1 more Smart Citation
“…Asterisks indicate the relevant bands. Ching et al, 2012) in N. tabacum suspension-cultured cells (Supplemental Fig. S3B), reconfirming that the XBAT35.2-containing structures were Golgi and not peroxisomes, which generally can resemble one another based on their appearance via confocal microscopy.…”
Section: Xbat352 Localizes Predominantly To the Golgi In Arabidopsismentioning
confidence: 74%
“…pMDC32/Cherry-PTS1, consisting of the Cherry red fluorescent protein linked to a C-terminal type 1 peroxisomal targeting signal, has been described elsewhere (Ching et al, 2012). Constructs were introduced into tobacco leaves or suspension cell cultures as described above.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Preferentially, GLYR1 catalyzes the NADPH-based reduction of glyoxylate into glycolate, and it has been proposed that glyoxylate detoxification by GLYR1 could provide an alternative sink for excess electrons during the recycling of reducing equivalents (121). Yet recently it was shown that the GLYR1 protein is exclusively present in the cytosol and is not found in the peroxisome (122). As GABA is converted to succinate semialdehyde in the mitochondria, GLYR1 could thus be involved in the detoxification of glyoxylate that accidently reaches the cytosol.…”
Section: Constitutive De Novo Synthesis Of Enzymes Involved In Energymentioning
confidence: 99%
“…Other previously described plant expression vectors include the following plasmids: pRTL2/RFP, encoding the red fluorescent protein (RFP) (36); pUC18/GFP-Syp21 and pUC18/GFPSyp52, which encode GFP fused to the N termini of the Arabidopsis membrane-bound Qa-SNAREs (soluble N-ethylmaleimide-sensitive factor attachment protein receptors) Syp21 (Syntaxin of plants 21) and Syp52 (37) proteins (kindly provided by M. Sato [Kyoto University]); pSAT2/Cherry-PTS1, encoding the monomeric cherry fluorescent protein fused to the C-terminal 10 amino acid residues of pumpkin hydroxypyruvate reductase, including its type 1 peroxisomal targeting signal (38); pRTL2/TIC40-RFP, encoding the Arabidopsis 40-kDa component of the translocon at the inner membrane of chloroplasts fused to the N terminus of RFP (39); and pSAT4A/AtPAP26-mCherry, encoding the Arabidopsis purple acid phosphatase isoform 26 fused to the N terminus of the monomeric cherry fluorescent protein (40). Yeast two-hybrid expression vectors, pGADT7 and pGBKT7 (Clontech) encoding Arabidopsis Vps23, Vps25, Vps37, and Vps28 were also previously described (35).…”
Section: Methodsmentioning
confidence: 99%